Association between caesarean section and childhood asthma development - Musiał, Lena; Możdżyńska, Agnieszka; Pawłocik, Weronika; Wojtala, Laura; Szymańska, Julia; Pawlak, Weronika; Grabowska, Ewa; Kapłon, Kamil; Rymarz, Anna; Kojder, Dominika (Journal of Education, Health and Sport, 2023)
According to the World Health Organization (WHO), the rates of caesarean section delivery, which is the most common surgical procedure in gynecology and obstetrics, are increasing globally and amount to 21%. In Poland percentage of caesarean sections (CS) is one of the highest in Europe and amount to 42.2%. The reason for this is the extension of medical indications, but also an increase in the number of CS at the request of pregnant women. Although CS can be a lifesaving procedure, it can also cause many health complications for both - the woman and the child. Numerous studies indicate that caesarean delivery is associated with childhood asthma. Several hypotheses of the pathogenesis of this relationship have been presented. One of them, which is based on the hygiene hypothesis indicates that mode of delivery can cause different bacteria colonization in infants. Lack of contact of fetus with the mother’s vaginal flora during CS labor may cause improper immune system maturation. Another hypothesis is that reduced exposure to stress hormones and mechanical forces during CS labor can indicate infant respiratory complications such as respiratory distress syndrome (RDS) or transient tachypnea of the newborn (TTN). It is suggested that these abnormalities have an impact on asthma development in later life. On the other hand, there are studies which do not confirm that mode of delivery has an influence on the induction of asthma. Due to the significant heterogeneity of studies and unclear risk factors and pathomechanism of the childhood asthma it is impossible to strong confirm the association between caesarean section and asthma developing.